UINSU Stambuk 2020 Communication Science Students' Perception of Persuasive Communication Through the Shopee Live Feature on Buyer Decisions - Anggi, Anggi (Universitas Ibn Khaldun, 2024)
This study aims to analyze the perception of UINSU Communication Science students class of 2020 towards persuasive communication carried out through the Shopee Live feature and its impact on buyer decisions. The research was conducted by collecting data through interviews conducted with UINSU Communication Science students who actively use the Shopee platform and have participated in live events organized by sellers on the platform. The data analysis methods used are descriptive analysis and regression analysis to determine the relationship between persuasive communication through Shopee Live and buyer decisions. Based on the results of research, the majority of the Communication Science students class of 2020 UINSU have a positive perception of persuasive communication delivered through the Shopee Live feature. The use of appropriate persuasive communication techniques in this feature has the potential to influence purchasing decisions, encouraging consumers to buy products offered by sellers in Shopee Live sessions.